Magnetic damping phenomena in ferromagnetic thin-films and multilayers. (25th October 2017) - Azzawi, S; Hindmarch, A T; Atkinson, D
Abstract: Damped ferromagnetic precession is an important mechanism underpinning the magnetisation processes in ferromagnetic materials. In thin-film ferromagnets and ferromagnetic/non-magnetic multilayers, the role of precession and damping can be critical for spintronic device functionality and as a consequence there has been significant research activity. This paper presents a review of damping in ferromagnetic thin-films and multilayers and collates the results of many experimental studies to present a coherent synthesis of the field. The terms that are used to define damping are discussed with the aim of providing consistent definitions for damping phenomena. A description of the theoretical basis of damping is presented from early developments to the latest discussions of damping in ferromagnetic thin-films and multilayers. An overview of the time and frequency domain methods used to study precessional magnetisation behaviour and damping in thin-films and multilayers is also presented. Finally, a review of the experimental observations of magnetic damping in ferromagnetic thin-films and multilayers is presented with the most recent explanations. This brings together the results from many studies and includes the effects of ferromagnetic film thickness, the effects of composition on damping in thin-film ferromagnetic alloys, the influence of non-magnetic dopants in ferromagnetic films and the effects of combining thin-film ferromagnets with various non-magnetic layers in multilayered configurations.